A tower of giraffes - Barth, Kelley (Childs World Inc, 2024)
This book introduces readers to giraffes and their family groups. Find out where they live and how they work together, and learn why they are called a tower. Additional features to aid comprehension include an activity or craft, a phonetic glossary, infographics, sources for further research, and critical thinking questions to help readers connect with the text.
590L
Decoding demand: 82 (very high) Semantic demand: 91 (very high) Syntactic demand: 80 (high) Structure demand: 81 (very high)
Keywords: Giraffe; Giraffe -- Juvenile literature